Video documental: K-POP y la creación de nuevos imaginarios a partir de ésta cultura en los jóvenes adolescentes, de la Ciudad de Quito que integran el grupo "Teukipop" - Dávalos Sevilla, Andrea Marjorie (2015)
The k-pop is a musical genre that has the ability to cross oceans, break the language barriers and reach the hearts of the fans who see it as a lifestyle. It is native from Asia, South Korea, is a musical style that draws the attention of young people and teenagers by the combination of catchy rhythms, dancing and a very particular fashion whit colors and glitter highlights. The k-pop came to invade Latin America from the "Korean Wave" or "Hallyu", as it is known, this is a project that the Korean government proposed to introduce Korean Culture and go forward through own efforts. Today in Quito-Ecuador have been formed several groups that give great importance to this genre, fan clubs have formed around the most important musical artists and groups from South Korea. K-pop is considered a lifestyle among young Teukipop group since it is from. This genre that have created an identity based on union, perseverance, brotherhood and never give up.